Computational modelling of creep-based fatigue as a means of selecting lead-free solder alloys - Steve Brown (Thermal, Mechanical and Multi-Physics Simulation and Experiments in Microelectronics and Microsystems (EuroSimE), 2013 14th International Conference on, 2013)
This investigation looked at the effect of temperature fluctuations on a number of solders used for varying joint configurations. Three different joint assemblies (a ball joint, a test specimen joint and finger lead joint) were chosen to simulate the creep and fatigue behaviours of various solder alloys including SAC105, SAC305, SAC405 and Sn-36Pb-2Ag. Both the impacts of thermal power cycles (80 to 150 °C) and thermal sh°Ck cycles (−40 to 125 °C) on solders were simulated by using the constitutive equation based on Anand's viscoplasticity model. From these results, lifetime-predictions of solder joints were derived using Coffin Manson procedures.